An analysis of anterior segment development in the chicken eye. (April 2018) - Trejo-Reveles, Violeta; McTeir, Lynn; Summers, Kim; Rainger, Joe
Abstract: Precise anterior segment (AS) development in the vertebrate eye is essential for maintaining ocular health throughout life. Disruptions to genetic programs can lead to severe structural AS disorders at birth, while more subtle AS defects may disrupt the drainage of ocular fluids and cause dysregulation of intraocular pressure homeostasis, leading to progressive vision loss. To date, the mouse has served as the major model to study AS development and pathogenesis. Here we present an accurate histological atlas of chick AS formation throughout eye development, with a focus on the formation of drainage structures. We performed expression analyses for a panel of known AS disorder genes, and showed that chick PAX6 was localized to cells of neural retina and surface ectoderm derived structures, displaying remarkable similarity to the mouse. We provide a comparison to mouse and humans for chick AS developmental sequences and structures and confirm that AS development shares common features in all three species, although the main AS structures in the chick are developed prior to hatching. These features enable the unique experimental advantages inherent to chick embryos, and we therefore propose the chick as an appropriate additional model for AS development and disease. Highlights: The chick is a resurgent developmental biology model due to novel genetic tools and inherent experimental accessibility We establish the chick as an additional model for development at the anterior segment (AS) We found common overlaps between chick, mouse and human AS development. In chick, these processes occur prior to hatching, whereas in mice these events continue to occur long after birth. We propose the chick to useful for investigating AS disorders, e.g. AS dysgenesis and primary open angle glaucoma.